Abordagem diagnóstica e terapêutica de cães com doença renal crônica com ênfase na hiperfosfatemia - Queiroz, Layla Livia de (2016)
Chronic kidney disease (CKD) is a degenerative condition that mainly affects older dogs. It has a progressive character, no cure, and in most cases is diagnosed late, when treatment becomes ineffective and survival timeshorter. With the objective of diagnosis’ standardization, the International Renal Interest Society (IRIS) proposed a staging system based on serum creatinine. One of the major complications of CKD is hyperphosphatemia, which is demonstrably linked to mortality inhuman patients. The presentstudy used 65 dogs with CKD, followed upmonthly. The mortality rate was 55% and the average age was seven years. The follow-up time ranged from 46 to 225 days. As for the IRIS staging, 6.2% of dogs were in stage 1, 13.8% in stage 2, 38.5% in stage 3 and 41.5% in stage 4. With the progression of disease, proteinuria and arterial blood pressureincreased while urine specific gravity reduced. Most of the dogs showed increased renal echogenicity and changes in cortico-medullary definition,in ultrasonographic examinations. Hyperphosphatemia occurred mainly in stages 3 and 4 and was related to progression of the disease, hypoalbuminemia, proteinuria, hypertension and increased mortality. Renal diet given continuously was effective in controlling hyperphosphatemia and increased survival time of dogs with CKD.